"Reduction" responsive thymine-conjugated biodynamers: synthesis and solution properties1. Issue 21 (7th June 2015) - Liu, Lingzhi; Wu, Libin; Tan, Junyan; Wang, Lin; Liu, Qing; Liu, Pingwei; Liu, Li
<x xml:space="preserve">Abstract</x> Nucleobase-conjugated biodynamers are generated by RAFT polymerization and the transthioesterification reaction. The biodynamers containing thioester linkages demonstrate GSH-responsive feature, and can interact with melamine and ATP in water.